Effectiveness of Competency Based Learning Models in Computer Networks Learning - Raimon Efendi; Jalius Jama; Asmar Yulastri (International Journal of Educational Dynamics, 2019)
Based on the studies and preliminary studies that have been conducted, the research problems are as follows: The personality (needs) of lecturers and students in the learning process of computer networks shows that they have high expectations of the learning process. Where are their expectations of the learning process that is able to improve 21st century competencies (critical thinking, communication, collaboration, creativity). The process and achievements of computer network courses have not been optimal. The purpose of developing a learning model of competency based learning is to help educators realize the learning process that is able to optimize the role of students in constructing their knowledge, through real experiences students get in the learning process. The design of the development of this competency based learning model uses the ADDIE model. Data was collected by questionnaires, observations, interviews and tests. Data is analyzed using quantitative and qualitative methods (mix method) so that learning is obtained through empirical and comprehensive studies. Based on the analysis carried out all products are declared valid, practical, and effective. The results of this study can be used by lecturers, and learning designers in developing or realizing the learning process that is able to optimize the role of students to be creative and innovative in building students' knowledge and competencies in the learning process.